Cognitive Behavioural Therapy through PowerPoint: Efficacy in an Adolescent Clinical Population with Depression and Anxiety - Nazanin Alavi; Matthew Stefanoff; Alyssa Hirji; Sarosh Khalid-Khan (International Journal of Pediatrics)
Background. Limited help-seeking behaviours, among adolescents with mental health concerns and many barriers to accessing mental health services, make innovative approaches to administering mental health therapies crucial. Therefore, this study evaluated the efficacy of e-CBT given via PowerPoint slides to treat adolescents with anxiety and/or depression. Method. 15 adolescents referred to an outpatient adolescent psychiatry clinic to treat a primary DSM-IV diagnosis of anxiety and/or depression chose between 8 weeks of e-CBT (n=7) or 7 weeks of live CBT (n=8). The e-CBT modules were presented using PowerPoint delivered weekly through email by either a senior psychiatry resident or an attending physician. Within each session, participants in both groups had personalized feedback on their mandatory weekly homework assignment from the previous week’s module. BYIs were completed before treatment and and after final treatment within both groups to assess changes in depression, anxiety, anger, disruption, and self-concept. Findings. Before treatment, BYI scores did not sig. differ between groups. After treatment, e-CBT participants reported sig. improved depression, anger, anxiety, and self-concept BYI scores while live CBT participants did not report any sig. changes. Only the Beck Anxiety Inventory sig. differed between groups after CBT. Conclusion. Despite the low sample size within this study, using email to deliver e-CBT PowerPoint slides and individualized homework feedback shows promise as an alternate method of CBT delivery that reduces barriers to receiving mental health treatment that occur internationally.